Changes in Oxidative Stress, Inflammation, and Muscle Damage Markers Following Diet and Beetroot Juice Supplementation in Elite Fencers - Lucyna Kozłowska; Olga Mizera; Jolanta Gromadzińska; Beata Janasik; Karolina Mikołajewska; Anna Mróz; Wojciech Wąsowicz (MDPI AG, 2020)
The aim of this study was to assess the impact of diet and active substances in beetroot juice on the parameters of oxidative stress, inflammation, and muscle damage as well as on the maximum rate of oxygen uptake (VO2max) in elite fencers (10 women, 10 men). Athletes during four weeks realized dietary recommendations (ID) and, after that, diet with freeze-dried beetroot juice supplementation (ID&BEET). At baseline and after each stage, fasting antioxidants, biomarkers of oxidative stress, inflammation, and skeletal muscle damage were measured, and a VO2max test was performed. Only after ID&BEET was a significant increase of VO2max observed, and changes of this parameter were negatively related with changes of serum lactate dehydrogenase (∆LDH) activity, as well as with serum ∆β-carotene and malondialdehyde concentration (∆MDA). Additionally, positive relationships were observed between ∆β-carotene versus changes of the serum concentration of advanced oxidation protein products (∆AOPP), changes of serum glutathione peroxidase activity (∆GPx3) versus both changes of physical activity level and ∆LDH, as well as erythrocyte glutathione peroxidase activity (∆GPx1) versus ∆LDH. To summarize, we showed that long-term beetroot juice supplementation increases lipid peroxidation, and improvement of VO2max after ID&BEET seems to be dependent on LDH activity, as well as on the serum concentration of MDA and β-carotene.